2017
DOI: 10.1038/onc.2017.362
|View full text |Cite
|
Sign up to set email alerts
|

‘MCC’ protein interacts with E-cadherin and β-catenin strengthening cell–cell adhesion of HCT116 colon cancer cells

Abstract: E-cadherin and β-catenin are key proteins that are essential in the formation of the epithelial cell layer in the colon but their regulatory pathways that are disrupted in cancer metastasis are not completely understood. Mutated in colorectal cancer (MCC) is a tumour suppressor gene that is silenced by promoter methylation in colorectal cancer and particularly in patients with increased lymph node metastasis. Here, we show that MCC methylation is found in 45% of colon and 24% of rectal cancers and is associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 54 publications
0
37
0
1
Order By: Relevance
“…In another experiment, we showed that a single DB pre-treatment (below IC50) could significantly reduce the tumor-initiating ability of IGF1-cultured DLD-1 colon CSC-like cells in vivo. Mechanistically, DB treatment was associated with the decreased expression of a key CSC marker, β-catenin, which has been shown to be aberrantly increased in malignant colon cancer cells and associated with the generation of drug-resistance [ 36 , 37 ]. DB-mediated suppression of β-catenin was also accompanied with an increased miR-214 level, which has a potential binding site at β-catenin’s 3′UTR.…”
Section: Discussionmentioning
confidence: 99%
“…In another experiment, we showed that a single DB pre-treatment (below IC50) could significantly reduce the tumor-initiating ability of IGF1-cultured DLD-1 colon CSC-like cells in vivo. Mechanistically, DB treatment was associated with the decreased expression of a key CSC marker, β-catenin, which has been shown to be aberrantly increased in malignant colon cancer cells and associated with the generation of drug-resistance [ 36 , 37 ]. DB-mediated suppression of β-catenin was also accompanied with an increased miR-214 level, which has a potential binding site at β-catenin’s 3′UTR.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous published studies revealed the presence of MCC protein in assorted widely used cell lines by WB analysis. However, the precise subcellular localization of MCC was controversial with various conflicting reports (Arnaud et al, 2009;Benthani et al, 2018;Fukuyama et al, 2008;Matsumine et al, 1996;Pangon et al, 2010Pangon et al, , 2015Senda et al, 1997). This is due both to the dearth of published studies investigating (Fukuyama et al, 2008;Pangon et al, 2015).…”
Section: Proteinmentioning
confidence: 99%
“…Mcc is membrane associated and interacts with β-catenin and E-cadherin to strengthen cell adhesion in CRC cell lines (Benthani et al, 2018).…”
Section: Proteinmentioning
confidence: 99%
See 2 more Smart Citations